2019
DOI: 10.1017/s1368980019000958
|View full text |Cite
|
Sign up to set email alerts
|

Snacking characteristics and patterns and their associations with diet quality and BMI in the Childhood Obesity Prevention and Treatment Research Consortium

Abstract: Objective To describe snacking characteristics and patterns in children and examine associations with diet quality and BMI. Design Children’s weight and height were measured. Participants/adult proxies completed multiple 24-hour dietary recalls. Snack occasions were self-identified. Snack patterns were derived for each sample using exploratory factor analysis. Associations of snacking characteristics and patterns with Health Eating Index-2010 (HEI-2010) score and body mass index (BMI) were examined using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(100 reference statements)
1
11
0
Order By: Relevance
“…The second pattern identified in the IMPACT study was the Sandwich pattern. The observation that both dietary patterns for IMPACT were distinct from those derived in other COPTR studies is similar to previous research in COPTR which identified distinct snack-occasion-specific dietary patterns for IMPACT compared with the other COPTR studies (44) . Interestingly, the Sandwich pattern in IMPACT was similar to another pattern called 'Packed Lunch' that was previously observed at 7, 10 and 13 years of age in the Avon Longitudinal Study of Parents and Children in England (45) .…”
Section: Healthy Cluster Unhealthy Clustersupporting
confidence: 86%
“…The second pattern identified in the IMPACT study was the Sandwich pattern. The observation that both dietary patterns for IMPACT were distinct from those derived in other COPTR studies is similar to previous research in COPTR which identified distinct snack-occasion-specific dietary patterns for IMPACT compared with the other COPTR studies (44) . Interestingly, the Sandwich pattern in IMPACT was similar to another pattern called 'Packed Lunch' that was previously observed at 7, 10 and 13 years of age in the Avon Longitudinal Study of Parents and Children in England (45) .…”
Section: Healthy Cluster Unhealthy Clustersupporting
confidence: 86%
“…The current study presents an original assessment of mealspecific DP in Brazilian schoolchildren. Previous data in the literature had mostly focused on eating patterns at isolated time periods of the day, disregarding other eating occasions (20)(21)(22)(23) . Almost all children ate the traditional three main meals (breakfast, lunch and dinner), while more than twothirds of them reported eating the mid-afternoon snack, and about half of the children reported the mid-morning and evening snacks.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with 2-11-year-old American children, two snack patterns were identified using factor analysis: a meal-like pattern (higher factor loadings for non-starchy vegetables, meats and grains) and a beverage pattern (higher loadings for unsweetened milk and sugar-sweetened beverage). The authors observed a positive association between the meal-like pattern and the diet quality (23) .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Based in Family Systems Theory (FST), prior research has shown supportive and nurturing family interactions and parenting practices promote healthy behavioral outcomes, including healthier weight management practices and improved dietary habits among adolescents [5,[21][22][23][24]. Further, parental support for healthy eating has been associated with healthier dietary intake (e.g., increased fruit and vegetable intake, reduced sweetened beverages), as well as sustained weight loss among adolescents [21,25] In contrast, more restrictive family feeding practices (restricting child's access to foods), are associated with poorer dietary outcomes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%